KONSEP KECANTIKAN DAN PERAWATAN KULIT WAJAH ; STUDI ANALISIS MAHASISWA UNIVERSITAS NEGERI SURABAYA - Jayanti, Khusmira Dwi; Faidah, Mutimmatul; Wilujeng, Biyan Yesi; Kusstianti, Nia (Program Studi Pendidikan Tata Rias, 2025)
A woman and beauty are two inseparable things. The concept of beauty is often seen as a relativity. That is, each person's view of the concept of beauty is different. But at the same time, beauty is also a universal thing. This is because there are standards and criteria that are used as a benchmark to be considered beautiful. Almost all women want to look beautiful all the time. Although every woman's nature is instinctively beautiful, most women try hard to be beautiful. As with students who also want to look beautiful, one of the efforts made is facial skin care. This research aims to find out: 1) the concept of beauty according to students of Surabaya State University 2) the effort of facial skin care according to students of Surabaya State University. This research uses a qualitative approach using descriptive qualitative research methods. Data were collected through in-depth interviews. The research subjects were 10 active students of Surabaya State University. The data collection method used was interview. The analysis method uses data reduction, data presentation and conclusions. Based on the results of the data analysis, Based on the results of data analysis, it is found that the concept of beauty is interpreted as something broad and relative. Which means there is no same description for each individual in interpreting the concept of beauty. However, there are aspects that become benchmarks in formulating the concept of beauty, namely the conception of the concept of beauty, beauty criteria, and aspects of beauty types. And based on the data analysis, Based on the results of data analysis, it is found that the concept of facial skin care is understood as part of an effort to look beautiful. The perception of the importance of facial skin care is very diverse and not the same for each individual. However, it can be described into aspects that become the benchmark of understanding and facial skin care efforts made. These aspects are the place of treatment, budget/special funds, beauty products, and treatment motivation. Keywords : Beauty, Care, Facial Skin